Driving Customer Loyalty through Product and Digital Service Quality: The Mediating Role of Satisfaction in PLN Mobile - Alfi Diana Maryatia; Endang Tjajaningsih (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study explores the impact of product quality and digital service quality on customer loyalty, with customer satisfaction as an intervening variable, focusing on PT. PLN (Persero) UP3 Cikupa in Tangerang Regency. In an era marked by rapid digital transformation, the adoption of digital services like PLN Mobile, a mobile application introduced by PLN in 2016, has significantly impacted how the company interacts with its customers. This research aims to understand how product quality and digital services influence customer satisfaction and, subsequently, their loyalty to the company. A quantitative approach was used, involving the collection of primary data through questionnaires distributed to 100 respondents who were users of PLN Mobile in the study area. The study applies multiple regression analysis to test the relationship between the variables. The results indicate that both product quality and digital service quality have a significant positive impact on customer satisfaction. Furthermore, customer satisfaction acts as a mediator between these factors and customer loyalty. It was found that improvements in the quality of PLN Mobile's product features, usability, and service reliability directly enhance customer satisfaction, which in turn fosters customer loyalty. These findings highlight the importance of continuously improving digital products and services to maintain long-term customer relationships and enhance competitive advantage in the utility sector. Additionally, the research underscores the significance of integrating customer feedback and maintaining high service standards in digital platforms to meet the evolving expectations of customers in the digital age. This study contributes valuable insights into the strategic management of digital service quality and customer satisfaction in the energy sector, providing recommendations for PLN (Persero) to refine its service offerings and enhance customer loyalty.